Evolutionary analysis of CD300A and CD300C paired receptors in primates - Dias, Carolina; Levi-Schaffer, Francesca; Esteves, Pedro José (Frontiers in Immunology, 2025)
IntrodctionThe CD300 family comprises immunoglobulin superfamily receptors that regulate immune cell function through inhibitory or activating signals. CD300A and CD300C form a paired receptor system that recognizes shared ligands but mediates opposing effects: CD300A transduces inhibitory signals, whereas CD300C promotes activation.MethodsHere, we investigated the evolutionary history of these receptors in primates by analyzing 62 sequences from 33 primate species.ResultsUsing phylogenetic reconstruction, synteny analysis, functional motif conservation, and pseudogene identification, we found that CD300A is present in all species examined. In contrast, CD300C exhibits a dynamic evolutionary profile, with multiple independent pseudogenization events, functional impairments, and complete loss in some lineages like Hylobatidae and some species like Lemur catta.DiscussionThese contrasting patterns suggest that while CD300A plays an essential and irreplaceable role in immune regulation, the activating function of CD300C may be context-dependent or dispensable. Additionally, we identified evidence of gene conversion between CD300A and CD300C in several lineages, preserving extracellular domain similarity despite divergent signaling functions. Our findings highlight the complex evolutionary dynamics of the CD300 gene family and provide new insights into how primate immune systems adapt.